The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/ecoj.12430
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens, Weather Shocks and Civil Conflicts

Abstract: This article documents a statistically strong and quantitatively relevant effect of high exposure to infectious diseases on the risk of civil conflicts. The analysis exploits data on the presence and endemicity of multi-host vector-transmitted pathogens in a country, which is closely related to geoclimatic conditions due to the specific features of these pathogens. Exploiting within-country variation over time shows that this effect of pathogen exposure is significantly amplified by weather shocks. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Robustness to Accounting for Alternative Correlates of Conflict Incidence Table A.16 conducts a robustness check on the results from the baseline analysis of the reduced-form impact of contemporary population diversity on the quinquennial incidence of civil conflict in repeated cross-country data, as shown in Panel A of Table 4. Specifically, we additionally control for the potentially confounding influence of alternative distributional indices of intergroup diversity (e.g., Fearon, 2003;Esteban, Mayoral and Ray, 2012) and additional geographical correlates of conflict (e.g., Fearon and Laitin, 2003;Cervellati, Sunde and Valmori, 2017). The specifications examined in this table are identical to the fully specified baseline models reported in Panel A of Table 4, with the exception that in Columns 1-3 and 6-8 of the current analysis, each of the reported control variables is employed in lieu of the baseline control for ethnic fractionalization , whereas in Columns 4 and 9, the set of reported control variables replaces the baseline controls for both ethnic fractionalization and ethnolinguistic polarization (Desmet, Ortuño-Ortín and Wacziarg, 2012), in the interest of mitigating multicollinearity.…”
Section: A2 Robustness Checks For the Analysis Of Civil Conflict Incmentioning
confidence: 99%
“…Robustness to Accounting for Alternative Correlates of Conflict Incidence Table A.16 conducts a robustness check on the results from the baseline analysis of the reduced-form impact of contemporary population diversity on the quinquennial incidence of civil conflict in repeated cross-country data, as shown in Panel A of Table 4. Specifically, we additionally control for the potentially confounding influence of alternative distributional indices of intergroup diversity (e.g., Fearon, 2003;Esteban, Mayoral and Ray, 2012) and additional geographical correlates of conflict (e.g., Fearon and Laitin, 2003;Cervellati, Sunde and Valmori, 2017). The specifications examined in this table are identical to the fully specified baseline models reported in Panel A of Table 4, with the exception that in Columns 1-3 and 6-8 of the current analysis, each of the reported control variables is employed in lieu of the baseline control for ethnic fractionalization , whereas in Columns 4 and 9, the set of reported control variables replaces the baseline controls for both ethnic fractionalization and ethnolinguistic polarization (Desmet, Ortuño-Ortín and Wacziarg, 2012), in the interest of mitigating multicollinearity.…”
Section: A2 Robustness Checks For the Analysis Of Civil Conflict Incmentioning
confidence: 99%
“…The IV F-stat decreases to 12.6, and the coefficients (-1.07** and 0.05) are close to our OLS estimates. 36 34 Relatedly, Cervellati et al (2014) show that in the post-World War 2 period disease outbreaks are associated with an intensification of civil conflict. Arguably, the respective number of soldiers involved, and whether the cities were burned or sacked, may be a better proxy for the devastation associated with warfare.…”
Section: Spatial Fixed Effectsmentioning
confidence: 99%
“…There are externalities to conflict from better health as well. Indeed, worse health (proxied by high exposure to infectious diseases) has been found to increase the risk of conflict (Cervellati, Sunde, and Valmori 2014).…”
Section: Externalitiesmentioning
confidence: 99%
“…Empirical studies of conflict have indeed found that welfare expenditures are associated with a lower risk of conflict (Bodea, Higashijima, and Singh 2016); education reduces the risk of civil war (Barakat and Urdal 2009;Collier and Hoeffler 2004;Østby and Urdal 2010;Thyne 2006); and where people suffer from poor health, there is more scope for conflict (Cervellati, Sunde, and Valmori 2014). Human capital can reduce the scope for conflict and the level of political instability through three channels, which are discussed next (Rohner 2014).…”
Section: Human Capital As a Conflict Deterrentmentioning
confidence: 99%